2020
DOI: 10.1371/journal.pone.0233174
|View full text |Cite
|
Sign up to set email alerts
|

Collagen methionine sulfoxide and glucuronidine/LW-1 are markers of coronary artery disease in long-term survivors with type 1 diabetes. The Dialong study

Abstract: Objectives Type 1 diabetes is a risk factor for coronary heart disease. The underlying mechanism behind the accelerated atherosclerosis formation is not fully understood but may be related to the formation of oxidation products and advanced glycation end-products (AGEs). We aimed to examine the associations between the collagen oxidation product methionine sulfoxide; the collagen AGEs methylglyoxal hydroimidazolone (MG-H1), glucosepane, pentosidine, glucuronidine/LW-1; and serum receptors for AGE (RAGE) with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Hence, it is indispensable to seek a convenient and noninvasive detection method [12]. Relevant studies have shown that CML, sRAGE, and esRAGE participate in the development of atherosclerosis [13,14], but few scholars shared the experience of evaluating the correlation among CML, sRAGE, and esRAGE and the measure of atherosclerosis in CHD. e outcome of this research found out that CML, sRAGE, and esRAGE were closely associated by the extent of atherosclerosis in CHD, and the reasons are analyzed as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is indispensable to seek a convenient and noninvasive detection method [12]. Relevant studies have shown that CML, sRAGE, and esRAGE participate in the development of atherosclerosis [13,14], but few scholars shared the experience of evaluating the correlation among CML, sRAGE, and esRAGE and the measure of atherosclerosis in CHD. e outcome of this research found out that CML, sRAGE, and esRAGE were closely associated by the extent of atherosclerosis in CHD, and the reasons are analyzed as follows.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our previous finding that Met-sulfoxide and 5-oxoproline declined during the aggravation of IL1-β-induced HGF inflammation by TiO 2 nanoparticles ( Supplementary Figure S2A,B , cited from [ 15 ]). Since Met-sulfoxide [ 23 , 24 , 25 ] and 5-oxoproline [ 26 , 27 , 28 ] are well-known markers reflecting oxidative stress, SE might have induced the cells to fight against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adding plasma endostatin to a basic model constructed with conventional factors significantly improved risk stratification in this population [ 46 ▪ ]. The collagen advanced glycation end product glucuronidine/LW-1 found in skin, rather than in the circulation, was also associated with established coronary heart disease and calcified plaque volume in diabetic patients [ 47 ▪ ].…”
Section: Collagen Structure and Plaque Integritymentioning
confidence: 99%